Diagnostic Utility of Procalcitonin for Sporadic Medullary Thyroid Carcinoma in Patients with Nodular Disease and Mild or Moderate Hypercalcitoninemia - Rosario, Pedro Weslley; Mourão, Gabriela Franco (Hormone and Metabolic Research, 2022)
Many authors recommend the measurement of serum calcitonin (Ctn) to screen for sporadic medullary thyroid carcinoma (MTC) in patients with thyroid nodules. In this situation, procalcitonin (pro-Ctn) would have greater utility in patients with hypercalcitoninemia<100 pg/ml. The aim of this study was to evaluate the utility of pro-Ctn in patients with thyroid nodules and without a suspicion of familial MTC or type 2 multiple endocrine neoplasia who had mild or moderate hypercalcitoninemia without an apparent cause. Consecutive patients with nodular thyroid disease assessed routinely by Ctn measurement were selected. Sixty patients with basal Ctn>10 pg/ml but<100 pg/ml were included. Nine patients (15%) had MTC, with cytology being diagnostic in only four. Among the 51 patients without MTC, pro-Ctn was<0.1 ng/ml in 46 (90.2%). All patients with MTC had pro-Ctn>0.1 ng/ml. Basal Ctn was>24.6 pg/ml in all patients with MTC and in 42 patients (82.3%) without MTC. It is noteworthy that among patients with basal Ctn>24.6 pg/ml (n=18) pro-Ctn>0.1 ng/ml identified all patients with MTC and 64.2% of subjects with these pro-Ctn concentrations had this tumor. In conclusion, we did not find superiority of pro-Ctn over Ctn for the diagnosis of sporadic MTC in patients with nodular disease and mild or moderate hypercalcitoninemia. However, in the case of patients with hypercalcitoninemia in the gray zone, pro-Ctn has an excellent negative predictive value while the data regarding its positive predictive value are not uniform.
Keywords: thyroid nodule; hypercalcitoninemia; procalcitonin; medullary; thyroid carcinoma